The limited role of expectancy-value beliefs, self-efficacy, and perceived attentional control in predicting online learning outcomes in a general education course - Roberts, Raoul A.; Gravelle, C. Donnan; Che, Elizabeth S.; Zapparrata, Nicolas; Lodhi, Arshia K.; Brooks, Patricia J. (Frontiers in Education, 2025)
IntroductionResearchers have expended enormous effort on understanding how college students’ intrapersonal beliefs contribute to their academic success.MethodsThis study used structural equation modeling to examine factors associated with course outcomes of students enrolled in an online general education course at a non-selective public college (16 sections, N = 940).ResultsStructural models linked students’ expectancy-value beliefs with academic self-efficacy, which in turn correlated with reading comprehension and self-reported attentional control. Both reading comprehension and self-reported attentional control predicted course outcomes whereas students’ expectancy-value beliefs and academic self-efficacy had no direct influence. Despite adequate model fit, students’ intrapersonal beliefs and skills collectively accounted for only 6.6% of the variance in course outcomes.ConclusionsIndividual-level variables may lack explanatory value in accounting for online learning outcomes, indicating the need to increase emphasis in educational psychology research on social and systemic factors affecting student success. Instructors should also recognize that factors besides intrapersonal beliefs and skills influence students’ persistence in online coursework and the need to support students at risk of dropping out.